The Influence of Credit Risk and Liquidity Risk on Profitability of State-Owned Bank (BUMN) - Retno Febriyastuti Widyawati; Ermatry Hariani; Yanis Ulul Az'Mi (Universitas Warmadewa, 2022)
Bank has an important role. As a financial institution that functions to collect and distribute of funds to the public, banking financial institutions are very vulnerable to risk in carrying out its activities. Therefore, this research aims to examine the influence of credit risk and liquidity of BUMN Bank in 2017:Q1Q4 to 2020:Q1Q4. This research used quantitative data with multiplier linear regression method. The unit of analysis studied consisted of three state owns banks in Indonesia: BRI, Bank Mandiri, and BNI. Periode 2017:Q1Q4 to 2020:Q1Q4. The data is taken form financial reports issued by the Financial Services Authority. The results show that credit risk (NPL) has a negative and insignificant effect on the profitability of state owned banks (ROA) in 2017:Q1Q4 to 2020:Q1Q4. Credit risk (NPL) and liquidity risk (LDR) simultaneously affect the profitability of state owned banks (ROA) in 2017:Q1Q4 to 2020:Q1Q4.